Application of IgY antibodies in passive immunization of aquaculture animals - Qiu, Hui-long; Jin, Xiao-min; Zhang, Xiao-mei; Wang, Feng-qin; Huang, Jia-qiang; Wang, Lian-shun (Frontiers in Physiology, 2025)
Chicken Egg Yolk Immunoglobulin (IgY) is a specific antibody found in egg yolk, offering several advantages, including low production cost, pollution-free processing, and no drug resistance. IgY as a passive immunotherapy agent in the field of aquaculture, the focus is on the prevention and control of common aquatic diseases, including vibriosis (Vibrio parahaemolyticus, Vibrio harveyi, Vibrio splendidus), bacterial septicemia (Aeromonas hydrophila, Aeromonas salmonicida), and viral diseases (Nervous Necrosis Virus, White Spot Syndrome Virus). The administration of specific IgY via feed, oral intake, immersion, or injection has been shown to significantly enhance antibody levels and phagocyte activity in shrimp, fish, sea cucumbers, and other aquatic animals. This approach has been demonstrated to reduce pathogen colonization, enhance immune performance, and decrease infection incidence and mortality rates. In the context of sustainable aquaculture development, IgY has emerged as a significant biological immunomodulator, with the potential to replace traditional antibiotics and control diseases in aquatic animals. This review summarizes the fundamental structure differences from IgG, physicochemical properties, and preparation methods of IgY, with a focus on its passive immunotherapy application progress in disease prevention, treatment, and immunization for freshwater and marine aquaculture animals. Finally, the positive effects of IgY on the quality and safety of aquatic products were discussed, with the aim of conducting in depth research on IgY and its widespread application in aquaculture.